2000
DOI: 10.1046/j.1365-2125.2000.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased dromotropic response to verapamil despite pronounced increased drug concentration in rheumatoid arthritis

Abstract: Aims In¯ammation reduces hepatic clearance of many drugs with unknown therapeutic consequences. This study was carried out to examine the effect of rheumatoid arthritis (RA) on the pharmacokinetics and pharmacodynamics of verapamil. Methods Eight RA patients were age-and sex-matched with eight healthy volunteers. The disease severity was assessed, and ECG, blood pressure and verapamil enantiomers concentrations were measured for 12 h post 80 mg oral verapamil. Serum interleukin-6 (IL-6) and nitrite (NO 2 ± ) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
136
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 43 publications
11
136
1
2
Order By: Relevance
“…As described previously, a systemic inflammatory response has been shown to be associated with the repression of Cyp3a activity (Shedlofsky et al, 1994;Mayo et al, 2000;Frye et al, 2002). In order to determine whether the presence of malignancy induced a systemic inflammatory response, the mRNA expression of the hepatic acute phase reactants, serum amyloid protein (Sap) and metallothionein were measured in tumour-bearing mice compared with controls.…”
Section: Evaluation Of Tumour-induced Inflammationmentioning
confidence: 99%
“…As described previously, a systemic inflammatory response has been shown to be associated with the repression of Cyp3a activity (Shedlofsky et al, 1994;Mayo et al, 2000;Frye et al, 2002). In order to determine whether the presence of malignancy induced a systemic inflammatory response, the mRNA expression of the hepatic acute phase reactants, serum amyloid protein (Sap) and metallothionein were measured in tumour-bearing mice compared with controls.…”
Section: Evaluation Of Tumour-induced Inflammationmentioning
confidence: 99%
“…Several reports have suggested that the pharmacokinetics of drugs such as atorvastatin (Kruger et al, 2009), erythromycin (Rivory et al, 2002), verapamil (Mayo et al, 2000) and propranolol (Ling and Jamali, 2005), which are metabolized by CYP3A subfamily enzymes, are altered in the patients with inflammatory diseases. For example, the serum concentrations of antihypertensive drugs, such as verapamil and propranolol, are higher in patients with rheumatoid arthritis than in healthy subjects or with mild disease (Mayo et al, 2000;Schneider et al, 1981).…”
Section: Il-6mentioning
confidence: 99%
“…For example, the serum concentrations of antihypertensive drugs, such as verapamil and propranolol, are higher in patients with rheumatoid arthritis than in healthy subjects or with mild disease (Mayo et al, 2000;Schneider et al, 1981). Likewise, decreases in the clearance of these antihypertensive drugs have been reported in rats with adjuvant-induced arthritis (Guirguis and Jamali, 2003;Ling and Jamali, 2005).…”
Section: Il-6mentioning
confidence: 99%
“…E.g. despite of very high plasma concentrations of the calcium channel blocker, verapmil, or potassium channel antagonists, sotalol or propranolol; no change in the PD was seen in inflamed animals (Guirguis & Jamali, 2003;Kulmatycki et al, 2001;Mayo et al, 2000). The authors concluded this to be due to altered receptor-functioning or receptor-ligand binding exhibited by inflammation.…”
Section: Pk/pd Studiesmentioning
confidence: 82%
“…Based on these early observations, recent studies have also shown altered PK of methotrexate, T-5557 (novel anti-inflammatory agent) and doxorubicin in AA animals (Achira et al, 2002a(Achira et al, , 2002b2002d). Although, a significant increase in the plasma concentrations of verapamil in rats and humans with underlying arthritis were reported, there were no changes in the PD of verapamil (prolongation of PR interval) (Mayo et al, 2000;Sattari et al, 2003). This discrepancy was then attributed to a decrease in the receptorligand affinity in inflammation (Laporte et al, 1998;Shore et al, 1997).…”
Section: Pk/pd Studiesmentioning
confidence: 97%